The Situation of State Management of Labor in Nghi Son Economic Area, Thanh Hoa Province, Vietnam - Quang, Nguyen Huu (International Journal of Humanities and Education Development (IJHED), 2023)
State management of labor plays a particularly important role in the socio-economic development of the country and the region. It is an important solution to improve the quality of labor resources, connect supply and demand, create jobs for workers, create wealth for society, generate income for themselves, and improve their lives. Constantly improving capacity and qualifications is also a condition for employees to enjoy achievements in culture and human civilization. Within the framework of this article, the author focuses on analyzing the current state of state management of labor in Nghi Son economic zone, Thanh Hoa province, Vietnam. On that basis, propose some solutions to improve the efficiency of the state management of labor in the study area the next time.